The Role of Physical Education Teachers in Character Education at Public Elementary Schools in Montong Gading - Azzohra, Trifia; Yundarwati, Susi; Wangi, Sekar Pudak; Irmansyah, Johan; Wasa, Carolus (Sportify Journal, 2025)
This study was motivated by elementary students’ behaviors that do not fully reflect positive character, such as lack of discipline, low empathy, impolite speech, and limited responsibility toward the school environment. The study aimed to describe the role of Physical Education, Sports, and Health teachers as a medium for character education in public elementary schools across Montong Gading District. This research employed a quantitative descriptive approach with a survey method. The sample included the entire population, namely 28 public elementary school physical education teachers, selected through total sampling. Data were collected using a closed-ended five-point Likert questionnaire and analyzed using descriptive statistics, including mean, standard deviation, frequency, percentage, and category classification. The results showed that teachers’ overall role was in the sufficient category at 42.86%. Exemplary behavior was the strongest factor, rated good at 64.29%, whereas motivator and evaluator roles remained sufficient.